The murderer lives at number 21 = L' assassin habite au 21 - Steeman, Stanislas-André 1908-1970; Yvain, Maurice 1891-1965 (Eureka Entertainment Ltd., 2013)
"Ein Kriminalkommissar wird beauftragt, eine Mordserie in Montmartre aufzuklären; er gibt sich als Pastor aus und mietet sich in einem Haus ein, in dem er auf seltsame Gestalten und noch eigentümlichere Vorfälle stößt. Schließlich stößt er auf eine verblüffende Lösung. Henri-Georges Clouzots erste Regiearbeit zeigt bereits die faszinierende Fähigkeit, filmisch zu erzählen, eine Dramaturgie zu entwickeln, den Zuschauer zu überlisten und mit der Beherrschung der Spannungselemente in den Bann zu ziehen." [filmdienst.de]
Original: Frankreich 1942
Bildformat 1.37:1
Gorgeous new Gaumont restoration of the film in its original aspect ratio, presented in 1080p ; newly translated optional English subtitles ; a new and exclusive video interview with French film scholar Ginette Vincendeau about Clouzot and its debut ; 28-page booklet with an essay about the film by scholar Judith Mayne; an extract about Occupation cinema from scholar Christoper Lloyd's book about Clouzot; newly translated interview extracts about the making of the film by Clouzot, source author Stanislas-André Steeman and actress Suzy Delair; a short testimonial by Jean Cocteau; and rare imagery
Keywords: Film; DVD-Video